A study about the 3D acceleration in front crawl and its relation with performance - Tella, V.; Madera, J.; Colado, J. C.; Mateu, J.; Garcia Masso, X.; Gonzalez, L. M. (Biomechanics and Medicine in Swimming XI, 2010)
The objective of this study was to analyze the acceleration of the hip generated during front crawl. The swimmers (n=71) performed 25 meters at maximum speed. 3D acceleration was registered. Swimming time domain acceleration signal was analysed. Root Mean Square (RMS) parameter was calculated in the three directions. Also, RMS indexes were calculated to relate the directions in twos. The results showed differences between the different parameters. Speed correlated positively with the RMS values: anterior-posterior (X), medium-lateral (Y) and superior-inferior (Z) directions (p<0.01). Also, statistical relations were found among the indexes that relate the X and Y (p<0.01) acceleration directions and the X and Z (p<0.01). To conclude, 3D acceleration analysis may indicate the efficiency during front crawl.